Ethnomedicinal uses of plants by the Lodhas tribal group of West Bengal, India - Sagari Chaudhury; Harish Singh; Chowdhury Habibur Rahaman (Journal of Traditional and Folk Practices (JTFP), 2018)
Lodhas of West Bengal utilize a diversified phyto-resources including forest flora for their survival. The ethnobotanical survey was undertaken in the selected Lodha populated villages of six districts of West Bengal, India during 2014-2017 with the objectives of documentation of the phyto-diversity used by the Lodhas and making an inventory to enrich the ethnobotanical data base of Lodha tribe, West Bengal. In this study, a total of 250 vascular plant species belonging to 83 families along with 728 ethnobotanical uses which belong to the 12 numbers of use categories have been documented. Highest number of species utilized by the Lodhas belongs to the family Leguminosae (28), followed by Poaceae (14), Asteraceae (11), Dioscoreaceae (10), etc. Some of the important plants used more frequently by the Lodha people in the state of West Bengal are Aristolochia indica L., Asparagus racemosus Willd., Dioscorea alata L., D. glabra R. Baron, Hemidesmus indicus (L.) R. Br. ex Schult., Solena amplexicaulis (Lam.) Gandhi, etc. A number of traditional practices still exists among the Lodhas which are employed for conservation of local biodiversity and to ensure the sustainable livelihood of the Lodha people.